Russia in Eurasia: between China and the West. Identity, Ideology and Geopolitics - A. V. Vinogradov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The genesis of the Russian civilization is inextricably connected with the Mongol conquests of the 13th century. From that moment, Russia acquired a binary, Euro-Asian identity, which allowed it to master large spaces of Eastern Europe and Northern Asia in a different way compared to other European nations mastered the spaces of Asia and Africa, and eventually create the largest Eurasian state. All of its subsequent development took place in the constant internal struggle of two origins -the West and the East, both of them attracted Russia, influenced its identity and created opportunities for development, which Russia managed to exploit successfully. Until now, geopolitics remains a trigger for internal change and the cause of the transformation of Russian identity. Disappointed with the Eurasian project and trying to reunite with the West at the end of the 20th century, Russia decided to abandon the “Asian burden” and at the same time its own type of historical development. However, Russia did not change its identity, but rejected it. As a result, it did not fit in, but fell out of global trends.The rise of China opened up new opportunities for Russia. The strategic cooperation and interaction of the two countries has become a powerful tool in their struggle for multipolarity and global status in rivalry with the West. But at the same time, it has given Russia a new geopolitical challenge. Today, China is ready to offer the Post-Soviet Central Asia an attractive socio-economic model and a familiar and acceptable ideology. Under global geopolitical changes Russia is facing the choice of a new development strategy, which could find ways of conjunction the “Russian world” with the European Union and the Chinese “Belt and Road”.